Pancreatic Involvement in Melioidosis - Chong, Vui Heng; Lim, Kian Soon; Sharif, Faizal (JOP. Journal of the Pancreas, 2010)
Context Melioidosis is endemic to tropical regions and, despite the common occurrence of intra-abdominal abscesses, pancreatic involvement in melioidosis has not previously been reported. Objective We report our experience with pancreatic melioidosis. Patients All 65 patients treated for melioidosis who had computed tomography (CT) scans were identified from prospective databases and were retrospectively reviewed. Main outcome measures A detailed review of cases with pancreas involvement was carried out. Results There were four cases (three males and one female; median age 29.5 years, range: 25-48 years) with pancreatic melioidosis, giving a prevalence of 6.2%. All had predisposing conditions (two had poorly controlled diabetes mellitus and two had thalassemia) for melioidosis. Fever (100%), anorexia (100%), weight loss (100%), rigor (75%) and abdominal pain (75%) were the most common symptoms at presentation and the median duration of symptoms before presentation was six weeks (range: 2-8 weeks). All pancreatic abscesses were detected on CT scan. Multiple foci involvement was common (3 to 6 sites): blood (4 patients), liver (3 patients), psoas muscle (2 patients), spleen (2 patients), infected ascites (2 patients) and lung (1 patient). Pancreatic involvement ranged from multi-focal micro-abscesses to focal large abscesses and involved all parts of the pancreas (body 100%, head 75% and tail 50%). Associated pancreatic findings included splenic vein thrombosis, peripancreatic inflammation and peripancreatic fat streaking. All the pancreatic abscesses were resolved with antibiotics without requiring pancreatic abscess drainage (including one patient who died from disseminated melioidosis). Conclusion Pancreatic involvement typically occurs as part of multi-organ involvement and commonly manifests as multifoci micro-abscesses. Associated pancreatic abnormalities were also common. All responded to treatment without requiring drainage. Image: Multiple abscesses in the body and tail regions of the pancreas, splenic vein thrombosis and splenic micro-abscesses.